Penentuan Kadar Flavonoid dan Vitamin C dalam Umbi Bawang Hutan (Eleutherine bulbosa (Mill) Urb) yang Berasal dari Desa Matantimali Kabupaten Sigi - Karmila, Karmila; Jura, Minarni R.; Tiwow, Vanny M. A. (Jurnal Akademika Kimia, 2018)
This study aimed to determine flavonoids and vitamin C levels contained in forest onion bulbs (Eleutherine bulbosa (Mill) Urb). Determination of the levels of flavonoids in forest onion bulbs extracted by maceration in etanol-HCl 1%, while vitamin C is extracted with 96% ethanol. Flavonoids and vitamin C levels in samples of forest onion bulbs were determined using UV-Vis spectrophotometer. The result showed that the flavonoids levels obtained was as much as 13.4058 mg/ 100 g, while vitamin C levels was as much as 31.678 mg/100 g.